Age of injury, emotional problems and executive functioning in understanding disrupted social relationships following childhood acquired brain injury. Issue 3 (19th August 2014) - Gracey, Fergus; Watson, Suzanna; McHugh, Meghan; Swan, Andrew; Humphrey, Ayla; Adlam, Anna-Lynne R; McNicholl, Declan; Wicks, Beth
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose Clinically significant childhood acquired brain injury (ABI) is associated with increased risk of emotional and behavioural dysfunction and peer relationship problems. This study sought to determine how emotional and peer related problems for children with ABI compare with those of children referred to mental health services, and to identify clinical predictors of peer relationship problems in a heterogeneous sample typical of a specialist community rehabilitation setting. Design/methodology/approach Participants were 51 children with clinically significant acquired brain injury (32 Traumatic Brain Injury; 29 male) referred for outpatient neuropsychological rehabilitation. Emotional, behavioural and social outcomes were measured using the Strengths and Difficulties Questionnaire (SDQ), and executive functioning was measured with the Behaviour Rating Inventory of Executive Functions (BRIEF). Correlational analyses were used to explore variables associated with peer relationships. A subgroup (n=27) of children with ABI were compared to an age and sex matched mental health group to determine differences on SDQ subscales. Findings The SDQ profiles of children with clinically significant ABI did not significantly differ from matched children referred to mental health services. Time since injury, peer relationship problems, metacognitive, and behavioural problems correlated with age at injury. These variables and SDQ emotional problems correlated with peer relationship problems. Linear multiple regression analysis indicated that only metacognitive skills remained a significant predictor of peer relationship problems, and metacognitive skills was found to significantly mediate between age of injury and peer relationship problems. Research limitations/implications The study confirms the significant effect of childhood ABI on relationships with peers and mental health, those injured at a younger age fairing worst. Within the methodological constraints of this study, the results tentatively suggest that age of injury influences later peer relationships via the mediating role of poor metacognitive skills within a heterogeneous clinical sample. Originality/value This is the first study to examine the roles of emotional, behavioural and executive variables on the effect of age at injury on peer relationship problems in a sample with a wide range of ages and ages of injury.